Management of Field-Evolved Resistance to Bt Maize in Argentina: A Multi-Institutional Approach - Signorini, Ana M.; Abratti, Gustavo; Grimi, Damián; Machado, Marcos; Bunge, Florencia F.; Parody, Betiana; Ramos, Laura; Cortese, Pablo; Vesprini, Facundo; Whelan, Agustina; Araujo, Mónica P.; Podworny, Mariano; et al. (Frontiers in Bioengineering and Biotechnology, 2018)
Evolution of resistance to control measures in insect populations is a natural process, and management practices are intended to delay or mitigate resistance when it occurs. During the 2012/13 season the first reports of unexpected damage by Diatraea saccharalis on some Bt maize hybrids occurred in the northeast of San Luis province, Argentina. The affected Bt technologies were Herculex I® (HX-TC1507) and VT3PRO® (MON 89034 × MON 88017*). Event TC1507 expresses Cry1F and event MON 89034 expresses Cry1A.105 and Cry2Ab2, whichr are all Bt proteins with activity against the lepidopterans D. saccharalis and Spodoptera frugiperda (MON 88017 expresses the protein Cry3Bb1 for control of coleopteran insects and the enzyme CP4EPSPS for glyphosate tolerance). The affected area is an isolated region surrounded by sierra systems to the northeast and west, with a hot semi-arid climate, long frost-free period, warm winters, hot dry summers, and woody shrubs as native flora. To manage and mitigate the development of resistance, joint actions were taken by the industry, growers and Governmental Agencies. Hybrids expressing Vip3A protein (event MIR162) and/or Cry1Ab protein (events MON 810 and Bt11) as single or stacked events are used in early plantings to control the first generations of D. saccharalis, and in later plantings date's technologies with good control of S. frugiperda. A commitment was made to plant the refuge, and pest damage is monitored. As a result, maize production in the area is sustainable and profitable with yields above the average.